A decision model to estimate a risk threshold for venous thromboembolism prophylaxis in hospitalized medical patients. (3rd May 2017) - Le, P.; Martinez, K. A.; Pappas, M. A.; Rothberg, M. B.
Abstract : Essentials Low risk patients don't require venous thromboembolism (VTE) prophylaxis; low risk is unquantified. We used a Markov model to estimate the risk threshold for VTE prophylaxis in medical inpatients. Prophylaxis was cost‐effective for an average medical patient with a VTE risk of ≥ 1.0%. VTE prophylaxis can be personalized based on patient risk and age/life expectancy. Summary: Background: Venous thromboembolism (VTE) is a common preventable condition in medical inpatients. Thromboprophylaxis is recommended for inpatients who are not at low risk of VTE, but no specific risk threshold for prophylaxis has been defined. Objective: To determine a threshold for prophylaxis based on risk of VTE. Patients/Methods: We constructed a decision model with a decision‐tree following patients for 3 months after hospitalization, and a lifetime Markov model with 3‐month cycles. The model tracked symptomatic deep vein thromboses and pulmonary emboli, bleeding events and heparin‐induced thrombocytopenia. Long‐term complications included recurrent VTE, post‐thrombotic syndrome and pulmonary hypertension. For the base case, we considered medical inpatients aged 66 years, having a life expectancy of 13.5 years, VTE risk of 1.4% and bleeding risk of 2.7%. Patients received enoxaparin 40 mg day −1 for prophylaxis. Results: Assuming a willingness‐to‐pay (WTP) threshold of $100 000/ quality‐adjusted life year (QALY), prophylaxis was indicated for an average medical inpatient with a VTE risk of ≥ 1.0% up to 3 months after hospitalization. For the average patient, prophylaxis was not indicated when the bleeding risk was > 8.1%, the patient's age was > 73.4 years or the cost of enoxaparin exceeded $60/dose. If VTE risk was < 0.26% or bleeding risk was > 19%, the risks of prophylaxis outweighed benefits. The prophylaxis threshold was relatively insensitive to low‐molecular‐weight heparin cost and bleeding risk, but very sensitive to patient age and life expectancy. Conclusions: The decision to offer prophylaxis should be personalized based on patient VTE risk, age and life expectancy. At a WTP of $100 000/QALY, prophylaxis is not warranted for most patients with a 3‐month VTE risk below 1.0%.